Managing Payment System Risk During the Transition From a Centrally Planned to a Market Economy - Hook, Andrew (IMF Working Papers; Working Paper ;, 1992)
The objectives and functions of payments systems in centrally planned economies are described and analyzed. These are compared to those of payments systems in market economies and to the characteristics of an ideal payments system. The dominant role of the state in the centrally planned economies meant that the state underwrote virtually all payments risk. With the withdrawal of the state, however, participants became exposed to credit, liquidity, and operational risks. In the transition, the central bank has a key role to play in payments systems. Areas where rapid improvements are possible are: accounting, clearing, settlement, netting and standardization.